Respuesta :

Answer:

x = 3 + sqrt(13) or x = 3 - sqrt(13) or B)

Step-by-step explanation:

Solve for x:

x^2 - 6 x - 4 = 0

Hint: | Solve the quadratic equation by completing the square.

Add 4 to both sides:

x^2 - 6 x = 4

Hint: | Take one half of the coefficient of x and square it, then add it to both sides.

Add 9 to both sides:

x^2 - 6 x + 9 = 13

Hint: | Factor the left hand side.

Write the left hand side as a square:

(x - 3)^2 = 13

Hint: | Eliminate the exponent on the left hand side.

Take the square root of both sides:

x - 3 = sqrt(13) or x - 3 = -sqrt(13)

Hint: | Look at the first equation: Solve for x.

Add 3 to both sides:

x = 3 + sqrt(13) or x - 3 = -sqrt(13)

Hint: | Look at the second equation: Solve for x.

Add 3 to both sides:

Answer: x = 3 + sqrt(13) or x = 3 - sqrt(13)